Perbaikan Postur Tubuh Pekerja UMKM dengan Intervensi Ergonomi Melalui Perancangan Kursi Fleksibel - Haryudiniarti, Ayu Nurul; Restuasih, Sinta; Harjiyanto, Kun Harjiyanto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Fatigue among workers is something that often occurs and the cause needs to be known, this condition occurs in Bojonegoro Cassava Chips MSMEs located in Depok. The processing are peeling, washing, chopping, soaking to packaging involves human labour with manually simple tools. The purpose of this study is to analyse the posture of workers at each workstation and to develop a proposal for improving work methods to minimise the risk of injury. The methods used are Nordic Body Map, anthropometric, design with Autocad and Autodesk Inventor. The results of the anthropometric are: elbow height in standing position 105.8 cm, thigh length from the buttocks to the tip of the knee 67.16 cm, knee height in both standing and sitting positions 51.39 cm, knee height from the floor to the base of the lower thigh 43.79 cm and hip width 50.55 cm.